Crosstalk between Oxidative Stress and Inflammation Induced by Ionizing Radiation in Healthy and Cancerous Cells - Mohammadgholi, Mohsen; Hosseinimehr, Seyed J. (Current Medicinal Chemistry, 2024)
Radiotherapy (RT) is a unique modality in cancer treatment with no replacement in many cases and uses a tumoricidal dose of various ionizing radiation (IR) types to kill cancer cells. It causes oxidative stress through reactive oxygen species (ROS) production or the destruction of antioxidant systems. On the other hand, RT stimulates the immune system both directly and indirectly by releasing danger signals from stress-exposed and dying cells. Oxidative stress and inflammation are two reciprocal and closely related mechanisms, one induced and involved by the other. ROS regulates the intracellular signal transduction pathways, which participate in the activation and expression of pro-inflammatory genes. Reciprocally, inflammatory cells release ROS and immune system mediators during the inflammation process, which drive the induction of oxidative stress. Oxidative stress or inflammation-induced damages can result in cell death (CD) or survival mechanisms that may be destructive for normal cells or beneficial for cancerous cells. The present study has focused on the radioprotection of those agents with binary effects of antioxidant and anti-inflammatory mechanisms IR-induced CD.
Keywords: cell death